Development of the Universal Working Equipment of the Excavator for Preparation of Materials Based on Waste during the Road Building - Ivan Georgiadi; Adil Kadyrov; Vyacheslav Kunaev (Communications, 2023)
The article proposes a technological line for recycling the blast-furnace slag. This line makes it possible to obtain the crushed stone for road building, which has high water and frost resistance. The design of replaceable working equipment of a single-bucket excavator, with replaceable working tools for loosening frozen slag in dumps and preparing it for use in road building, is proposed. The results of testing the manufactured replacement working equipment are presented. The results of mathematical processing of experimental data using the approximation method are presented, as well.